Metabolic syndrome and gastric cancer risk: a systematic review and meta-analysis. Issue 3 (May 2021) - Mariani, Marco; Sassano, Michele; Boccia, Stefania
Abstract : Introduction: Gastric cancer (GC) is the fifth diagnosed cancer worldwide and the third leading cause of death for cancer. Recent reports suggest that metabolic syndrome (MetS) has a role in etiology, progression or prognosis on GC. The aim of this study is to systematically review the evidence on the association between MetS and GC risk and prognosis. Methods: Literature search was performed using the electronic databases Pubmed, Web of Knowledge, Embase and Cinahl Complete until December 2019. Cohort and case-control studies were included. Study-specific association measures were pooled using a random-effect model. Results: A total of 14 studies included in the qualitative synthesis of which nine were meta-analyzed. The majority were cohort studies (92%) and set in Asia (57%). The pooled analysis reported no association between MetS and GC risk [hazard ratio (HR) 1.05, 95% confidence interval (CI) 0.92–1.18; I 2 = 74.2%, P < 0.001], however when the analysis was stratified according to the geographic area and sex, Western women with MetS had an increased risk of GC (HR 1.24, 95% CI 1.05–1.47; I 2 = 4.6%, P = 0.351). We did not observe an increased risk of unfavorable prognosis for individuals with MetS (HR 1.23, 95% CI 0.25–6.08). Conclusion: This systematic review and meta-analysis suggests that GC risk might be associated with MetS in women although larger studies are needed. Preventing and treating MetS, however, might have overall beneficial effect on several noncommunicable diseases and in this sense should be pursued. Abstract : Supplemental Digital Content is available in the text.